Nutritional and Phytochemical Composition of Bambara Groundnut (Vigna subterranea [L.] Verdc) Landraces in Kenya - Chelangat, Mercy; Muturi, Phyllis; Gichimu, Bernard; Gitari, Josiah; Mukono, Simon (UoEM, 2023)
Bambara groundnut (Vigna subterranea) is a highly nutritious legume with good drought tolerance attributes and is therefore a suitable candidate for food and nutritional security especially in drought prone areas. This study was conducted to determine the nutritional and phytochemical composition of seventeen Bambara groundnut landraces that were collected from Vihiga, Kakamega, Bungoma, Busia, and Kisumu Counties in Kenya. Prior to characterization, a field experiment was set up in Ishiara Ward in Mbeere North Sub-County in Embu County for two cropping seasons to standardize and multiply the seeds. The experiment was laid out in a Randomized Complete Block Design with three replicates. The harvested seeds were analyzed for their proximate, nutritional, and phytochemical composition using standard procedures. The moisture content ranged from 3.47 to 6.24%, total ash from 3.17 to 4.69%, crude protein from 21.18 to 26.00%, and fats from 4.56 to 7.02%. Iron levels ranged from 4.07 to 5.13 mg/100 g, sodium from 25.14 to 129.66 mg/100 g, potassium from 819.34 to 1,131.80 mg/100 g, and zinc from 0.06 to 0.42 mg/100 g. The tannin levels ranged from 0.01 to 0.04 mg/g, saponins from 0.82 to 1.06 mg/100 g, alkaloids from 0.01 to 0.12 mg/100 g, and flavonoids from 4.07 to 8.45 mg/100 g. The landraces BG-125, BS-148, and BS-145 with relatively higher nutrients composition and those with high levels of phytochemicals such as BS-104 and MU-137 are recommended to plant breeders for further selection and production of certified seeds. These selections will also be promoted to the farmers for production through various extension programs.
Research Article
Keywords: Groundnut